2010
DOI: 10.1016/j.pedn.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Korean Immigrant Discipline and Children's Social Competence and Behavior Problems

Abstract: The goal of this correlational study was to explore the relationship between Korean immigrant discipline (e.g., positive, appropriate, harsh discipline) and children's social competence and behavior problems. Self-report data were collected from 58 mothers and 20 fathers of children aged from three and eight. Only paternal harsh discipline was positively correlated with children's behavior problems. Among specific discipline strategies, maternal physical affection, correcting misbehaviors, and reasoning were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Korean American parental acceptancerejection was also found to significantly influence their adolescents' psychological problems (E. Kim, 2008b) and their children's social competence (E. Kim, Han, & McCubbin, 2007). Maternal kissing, hugging, correction of mistakes, and reasoning were linked to social competence of children while paternal harsh discipline (spanking, hitting) was related to children's conduct behavior problems (E. Kim, Guo, Koh, & Cain, 2010).…”
Section: Korean American Parental Acceptance-rejection and Controlmentioning
confidence: 98%
“…Korean American parental acceptancerejection was also found to significantly influence their adolescents' psychological problems (E. Kim, 2008b) and their children's social competence (E. Kim, Han, & McCubbin, 2007). Maternal kissing, hugging, correction of mistakes, and reasoning were linked to social competence of children while paternal harsh discipline (spanking, hitting) was related to children's conduct behavior problems (E. Kim, Guo, Koh, & Cain, 2010).…”
Section: Korean American Parental Acceptance-rejection and Controlmentioning
confidence: 98%
“…Studies found 41% of KA children had behavior problems while 35% of U.S. children experienced similar problems (Kim, Guo, et al., ; Webster‐Stratton & Hammond, ). KA children also scored significantly higher on depressive symptomatology than European American children (Nahm, ).…”
Section: Protective and Risk Factors Related To Ka Child Mental Healthmentioning
confidence: 99%
“…The most important protective and risk factors related to KA child mental health were parenting practices and acculturation. Protective parenting practices included parental warmth, reasoning, and expressions of affection through hugging/kissing and saying “I love you” (Kim et al., ; Kim, Guo, et al., ). In contrast, risk parenting factors included parental rejection, physical punishment, intergenerational acculturation conflicts, and parental depression (Kim, , 2008a, 2008b, , ; Kim & Cain, ; Kim, Cain, & McCubbin, ; Kim et al., ; Kim, Guo, et al., ).…”
Section: Protective and Risk Factors Related To Ka Child Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kim et al () found that maternal negative parenting practices were associated with increased risks for later internalising behavioural problems in adolescents, while paternal negative parenting practices were linked to an increase in adolescents' externalising behavioural problems. In contrast, in a sample of parents of children aged 3–8 years, Kim, Guo, Koh, and Cain () found that only paternal parenting practices (e.g., harsh discipline) were linked to child behaviour problems.…”
Section: Introductionmentioning
confidence: 99%